Overview of Stress Level Among the Students in Medical Faculty of North Sumatera University Odd Semester Academic Year 2012/2013 - V. Pathmanathan, Vilaseeni (e-jurnal Fakultas Kedokteran USU, 2013)
Lifestyle changes, academic achievement, a solid schedule of lectures, problem peers, adapt away from home for the first time and with the new environment can trigger the occurrence of stress in students. This study aims to describe the level of stress on the students of the Faculty of Medicine USU  academic year 2012/2013. Using a cross sectional descriptive methods, data is obtained using a questionnaire measuring instrument Daily Hassles and Stress Rating Scale to 100 students. Sampling technique which used  for this study is stratified random sampling method. A  computer program is used to analyzed the data. The results from 100 students of USU School of Medicine showed  as many as 35 people (35%) experiencing low stress level, 61 people (61%) have simple stress level and 4 people (4%) experiencing high stress level. By age anyway, the age group 19 and 20 years recorded the highest figure for the level of stress. When compared between men and women, men have higher stress. Management of Medical faculty are advised to encourage programs such as mental health counseling to help students deal with stress.   Keywords: stress levels, student, faculty of medicine, USU